CARP-1 functional mimetics: a novel class of small molecule inhibitors of cancer cell growth and metastasis - Ashour, Abdelkader Elbadawy Abbas (2019)
CARP-1/CCAR1 is a peri-nuclear phospho-protein which functions as a co-activator of the cell cycle regulatory anaphase promoting complex/cyclosome (APC/C) E3 ligase. CARP-1 functional mimetics (CFMs) are a class of small molecule compounds that inhibit CARP-1 binding with APC/C subunit APC-2. CFM-4, a lead compound, was found to be a potent antitumor agent that suppresses growth and metastasis of various tumor cells including medulloblastoma, neuroblastoma, malignant pleural mesothelioma, lung and breast cancers, in part by stimulating apoptosis. Recently, we examined the possible inhibitory effects CFM-4 against proliferation and metastasis of colorectal cancer (CRC). CRC constitutes one of the most aggressive malignancies worldwide. Existing anti-tumor treatments clinically applied for CRC include surgery, radiotherapy and chemotherapy. The high incidence of metastasis and toxic side effects of therapies, as well as low response rates of CRC to chemotherapy indicate that existing treatment methodologies remain unsatisfactory. Thus, it is crucial to develop more efficient and less noxious treatment modalities for this disease. In this recent study, we investigated the growth inhibitory potential of the CFM-4 on CRC and found that CFM-4 inhibits colon cancer cell proliferation in a dose and time dependent manner. Notably, CFM-4 was much more potent than the classical anti-colorectal cancer 5-fluorouracil. The growth inhibitory effects of CFM-4 against CRC cells were mediated at least in part by stimulating apoptosis, as indicated in our Annexin V/Propidium iodide (PI) apoptosis assay results. To molecularly assess the effects of CFM-4 as antitumor agent against human colorectal HT-29 cells, mRNA expression analysis by qPCR was also utilized. Results revealed upregulation of expression of caspase-8 and caspase-9, as well as p53 and its downstream targets, PUMA, Noxa, Smac which play a crucial part in promoting mitochondrial apoptotic pathway. Pro-apoptotic molecules known to initiate the extrinsic apoptotic pathway including TRAIL death receptors (DR4 and DR5) were also upregulated. These results suggest that CFM-4 induces both intrinsic and extrinsic pathways of apoptosis. The influence of CFM-4 on mRNA expression of the NF-B signaling inhibitor A20-binding inhibitor protein (ABIN1) was also assessed and revealed upregulated. Although CFM-4 did not significantly affect the expression of the PI3K downstream effector AKT, it remarkably upregulated the PI3K negative regulator PTEN. Moreover, we examined CFM-4 effects on colon cancer cell cycle and observed that CFM-4 has significantly induced G2/M phase arrest and dose-dependent increase in sub-G1 peak, indicative of apoptosis, of the cell cycle of the colon cancer HT-29 cells, further substantiating our Annexin V/PI apoptosis results. Furthermore, western blot analysis results revealed that CFM-4 enhanced expression of CARP-1, as well as the initiator caspase, caspase-8, and the executioner caspase, caspase-3. On the other hand, metastatic properties of the HT-29 CRC cells were reduced by CFM-4 through blocking their capabilities to form colonies, migrate and invade through the matrix-coated membranes. These results revealed that the potent antitumor and anti-metastatic properties of CFM-4 against CRC are due to collective pro-apoptotic, anti-proliferative and anti-invasive activities. Together our data warrants further investigations of CFM-4 as potential anti-tumor agent for CRC malignancy and metastasis.